2016
DOI: 10.1007/s00467-016-3349-x
|View full text |Cite
|
Sign up to set email alerts
|

Elementary immunology: Na+ as a regulator of immunity

Abstract: The skin can serve as an interstitial Na+ reservoir. Local tissue Na+ accumulation increases with age, inflammation and infection. This increased local Na+ availability favors pro-inflammatory immune cell function and dampens their anti-inflammatory capacity. In this review, we summarize available data on how NaCl affects various immune cells. We particularly focus on how salt promotes pro-inflammatory macrophage and T cell function and simultaneously curtails their regulatory and anti-inflammatory potential. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 102 publications
1
58
0
Order By: Relevance
“…Local Na + contents are known to impact homeostatic and inflammatory innate myeloid cell function (24,49). For instance, exposure of macrophages to HS¢ impaired the regulatory, antiinflammatory activity of macrophages (41), while increases in local Na + enhanced their antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Local Na + contents are known to impact homeostatic and inflammatory innate myeloid cell function (24,49). For instance, exposure of macrophages to HS¢ impaired the regulatory, antiinflammatory activity of macrophages (41), while increases in local Na + enhanced their antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium is involved in inflammation in hypertension and because sodium levels are in part regulated by the kidney, sodium links the kidney 104 to other systems including the integumentary system 105 .…”
Section: Sodium Hypertension and Inflammationmentioning
confidence: 99%
“…Several recent studies have shown that a high salt diet (HSD) in laboratory mice is pro-inflammatory (18). Excess NaCl in vitro was shown to enhance Th17 differentiation and activity via a p38 MAPK→NFAT5→SGK1 pathway, and that a HSD plus 1% NaCl-supplemented water exacerbates experimental autoimmune encephalitis (EAE) in mice (19, 20).…”
Section: Introductionmentioning
confidence: 99%